2020
DOI: 10.1038/s41419-020-02962-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells-derived exosomal microRNA-193a reduces cisplatin resistance of non-small cell lung cancer cells via targeting LRRC1

Abstract: Exosomes are small endogenous membrane vesicles that can mediate cell communication by transferring genetic materials. Based on that, exosomes have always been discussed as a cargo carrier for microRNA (miRNA) transportation. Accumulating data have reported the inhibitory effects of microRNA-193a (miR-193a) on non-small cell lung cancer (NSCLC) cell progression. However, the mechanisms of miR-193a delivery to cancer cells and miR-193a in exosomes have not been explored clearly in NSCLC. Given that, this work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 39 publications
2
82
0
Order By: Relevance
“…Elsewhere, exosomal miR-382-5p released from oral squamous cell carcinoma cells stimulated tumor cells migration and invasion ability [ 20 ]. In non-small cell lung cancer, BMMSC-derived exosomes transferred miR-193a to induce cisplatin resistance via suppressing LRRC1 [ 21 ]. In previous studies, miR-149-5p was found to be highly expressed in lung adenocarcinoma cells and influenced tumor cells metastasis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, exosomal miR-382-5p released from oral squamous cell carcinoma cells stimulated tumor cells migration and invasion ability [ 20 ]. In non-small cell lung cancer, BMMSC-derived exosomes transferred miR-193a to induce cisplatin resistance via suppressing LRRC1 [ 21 ]. In previous studies, miR-149-5p was found to be highly expressed in lung adenocarcinoma cells and influenced tumor cells metastasis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The membrane protein enables PLT-PPy-Dox to evade the attack of immune cells and precisely target the tumor, laser irradiation causes PPy to produce hyperthermia and ablate the tumor cells, and Dox is also released from the NPs to effectively destroy the tumor. In addition, after three consecutive PTT cycles, the temperature of the tumor tissue increases, and then the tumor cells are burned; Due to PLTM recognize and accumulate in the injured site, PLT-PPy-Dox is more gathered in the tumor site, which promotes the efficiency of PTT (Wu et al, 2020 ). Therefore, the strategy of using biomimetic materials and combination therapy in the treatment of tumors has significant effects and promising prospects.…”
Section: Cell Membrane-coated Nanoparticlesmentioning
confidence: 99%
“…Ying et al transfected miR-193a into BM-MSCs-EXOs to target focal adhesion kinase in colon cancer, which downregulated the expression of focal adhesion kinase and inhibited the invasion, migration and proliferation of colon cancer cells (François et al, 2019 ; Ying et al, 2020 ). In another study, BM-MSCs-EXOs carrying miR-193A promoted apoptosis in drug-resistant lung cancer cells by downregulating LRRC1 (Wu et al, 2020 ). However, few studies have examined the transport RNA of BM-MSCs-EXOs to tumor stem cells, which creates new and feasible carriers for tumor drug delivery and has the value of further exploration.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Besides, chemotherapy and radiation therapy could also directly affect exosome biogenesis and the content of exosomes with potential implications on therapy outcome. It should be noted that the function of exosomal RNA in drug resistance is complicated and some scholars claim that exosomal RNAs may also play a role in reducing drug resistance [ 88 ]. Apart from chemoresistance, exosomes are also found to be of great value in determining outcomes in radiation therapy and some studies suggested that exosomes may induce the radiation-induced bystander effect (RIBE) [ 89 ].…”
Section: Role Of Exosomal Rna In the Initiation And Development Ofmentioning
confidence: 99%